Conservação do bambu - Simão, Salim (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1958)
This paper brings to light new data on the absence of influence of lunar phases on the preservation of bamboo sticks. The author cut down for one and a half years (from - June 18, 1947 to December 30,1948) bamboos in every phase of the moon. With part of the sticks obtained a fence was built; the rest v/as kept under shelter. In the fence there were: 5 whole sticks with no preservative, 5 whole sticks with thanalith, 5 halved sticks with no preservative, 5 halved sticks with thanalith, all buried 10 centimeters in the soil. An equal number of the same types and in the same fence were kept upright 10 centimeters above the soil. Under shelter, in a shed, there was another group of sticks, 10 of each of the same four types. After 5 1/2 years no damage was observed in the fence for any treatment or any phase of the moon. On the other hand, for those bamboos kept under shelter the following numbers of perforated sticks were observed. Number of perforated sticks after 5 1/2 years Without Thanalith Thanalith Date of cutting Phase of the moon Whole Halved Whole Halved 8 - 25 - 47 Prime 0 3 0 0 9 - 29 - 47 Full 0 3 0 0 10 - 7 - 47 Wane 0 3 0 0 10 - 14 - 47 New 2 4 0 0 10 - 29 - 47 Full 0 5 0 0 11 - 6 - 47 Wane 3 3 0 0 11 - 13 - 47 New 0 1 0 0 4 - 1 - 43 Wane 3 5 0 0 8 - 27 - 48 Wane 1 3 0 0 10 - 10 - 48 Prime 1 3 0 0 Totals 10 36 0 0 So, among the 400 sticks kept under shelter, after 5 1/2 years, only 46 were perforated, all among those withe no preservative. No influence of lunar phase at cutting down of sticks seems to be present.